(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In the frame of archetype the natural, spatial and design attributes of landscape in India is studied and illustrated with examples from Braj, Pavagarh, village plans, and pilgrimage centres and that landscape symbols express all that a culture holds dear and externalise deeply felt emotions. It is further observed that as Indian society modernizes secular thinking in the workplace and public sphere replaces religiosity ordained tasks (Sinha, 2006a).The diversities, distinctions and desperateness scattered all over India and at the other end unifying forces of traditions made this country a web of cultural whole. It is with these characteristics in studying cultural geography of India emerges a variety of topics. In the present review emphasis is placed on research that has been conducted in or about India. The first attempt to review the literature on cultural geography of India is presented by Wescoat et al. (2003). In the evolution and growth of geography in India since late 1990s a cultural turn took place through reinterpreting the ancient Indian classics using multidisciplinary approaches and illustrating them with field studies and contemporary contextuality (cf. Wescoat, et al. 2003). Examining lndianness’ in geographical context is a subject of self-retrospection as well as re-assessment (Singh, R.P.B. 2008e). Presently, issues of conversation and contestation have received more attention, like fluidity and dynamics of tradition, lineages of art. inter-culturalism and the question of body, dimensions of woman power in India. legacy of Gandhian politics, the humanist perspective and the civilizing role of history, and the debate on science in post-independence India. The long-standing and continuing debate on Indian culture and on what constitutes ‘Indianness’ manifests itself in many ways. some more subtle than others.